2009
DOI: 10.1593/neo.81038
|View full text |Cite
|
Sign up to set email alerts
|

Pim-1 Kinase Expression Predicts Radiation Response in Squamocellular Carcinoma of Head and Neck and Is under the Control of Epidermal Growth Factor Receptor

Abstract: Pim-1 is an oncogenic serine/threonine kinase with poorly defined function in epithelial cancers. In this study, we determined 1) associations of Pim-1 expression with clinicopathological parameters including responsiveness to irradiation in squamocellular cancers of head and neck and 2) how Pim-1 expression is controlled subsequent to irradiation. Moderate to high expression of Pim-1 correlated to poor response to radiation therapy (P = .003). It is also associated to the expression of epidermal growth factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 28 publications
8
53
0
Order By: Relevance
“…Consistent with our previous data, it has been reported that PIM1 is overexpressed in malignant keratinocytes in head and neck squamous cell carcinoma (HNSCC) and moderate/high PIM1 expression levels tend to be associated with poor prognosis in HNSCC compared to low/negative PIM1 expression [25]. In addition, the expression of PIM1 is also significantly associated with the expression of EGFR, which has been previously demonstrated to promote radioresistance [25,26]. Because the classic prognostic markers such as tumor size, nodal status, or histological grade cannot be used to predict responses to radiotherapy, and there are currently no generally accepted clinical markers for predicting radiosensitivity, these results may have clinical implication.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our previous data, it has been reported that PIM1 is overexpressed in malignant keratinocytes in head and neck squamous cell carcinoma (HNSCC) and moderate/high PIM1 expression levels tend to be associated with poor prognosis in HNSCC compared to low/negative PIM1 expression [25]. In addition, the expression of PIM1 is also significantly associated with the expression of EGFR, which has been previously demonstrated to promote radioresistance [25,26]. Because the classic prognostic markers such as tumor size, nodal status, or histological grade cannot be used to predict responses to radiotherapy, and there are currently no generally accepted clinical markers for predicting radiosensitivity, these results may have clinical implication.…”
Section: Introductionsupporting
confidence: 91%
“…Under these conditions, PIM1-activated pPRAS40, AKT-activated pFOXO3a, and complexes formed by these two proteins and 14-3-3 could be key regulators of IR-induced radioresistance in NSCLC cells. Consistent with our previous data, it has been reported that PIM1 is overexpressed in malignant keratinocytes in head and neck squamous cell carcinoma (HNSCC) and moderate/high PIM1 expression levels tend to be associated with poor prognosis in HNSCC compared to low/negative PIM1 expression [25]. In addition, the expression of PIM1 is also significantly associated with the expression of EGFR, which has been previously demonstrated to promote radioresistance [25,26].…”
Section: Introductionsupporting
confidence: 90%
“…However, investigation of a larger sample set of breast cancers is warranted to further corroborate this. Previously, increased expression of PIM-1 among non-hematological malignancies has been associated with poor prognosis of patients with esophageal squamous cell carcinoma and shown to predict poor radiation response in squamocellular carcinoma of head and neck (Xie et al, 2006;Mumenthaler et al, 2009;Peltola et al, 2009;Liu et al, 2010). In sum, our data indicate that the proto-oncogene PIM-1 is a potential estrogen target in breast cancer cells and that the elevated PIM-1 expression is associated with the increased invasiveness of breast cancer tumors.…”
Section: Tablesupporting
confidence: 62%
“…Since Pim kinase expression has been associated with poor outcome in several different tumor types (Wright et al, 2003;Dave et al, 2006;Rossi et al, 2006;Zheng et al, 2008;Peltola et al, 2009;Warnecke-Eberz et al, 2009) al., 2009), inhibition of Pim kinases has evoked a lot of interest and inspired efforts has been conducted to inhibit the Pim kinases as a potential tragedy of cancer treatment. Moreover, the triple knockout Pim kinase mice are viable and fertile, which suggests that inhibition of the Pim kinase family could be possible without severe side effects (Mikkers et al, 2004).…”
Section: Discussionmentioning
confidence: 99%